"No one went into pharmacy ... to sell a lot of Coca-Cola. It's just sort of a necessary evil" - Community pharmacists' perceptions of front-of-store sales and ethical tensions in the retail environment - Stephanie Gellatly; Alexander Moszczynski; Lean Fiedeldey; Sherilyn Houle; Maxwell Smith; Ubaka Ogbogu; Debbie Rudman; Leia Minaker; Jacob Shelley (Elsevier, 2023)
Background: Community pharmacists are expected to uphold ethical duties to patients and society while maintaining independent businesses or fulfilling expectations of corporate owners. Canadian pharmacy colleges provide only indirect guidance on the retail setting of the profession. Little is known about whether pharmacists identify ethical issues in retail pharmacy or around the sales of non-drug products. Objective: This study sought to examine pharmacists' perceptions of their roles in health promotion, the factors that influence the selection of front-of-store products, and ethical issues relating to their dual roles as health care providers and retailers. Methods: In 2020, 25 Canadian pharmacists participated in semi-structured phone interviews. Interviews were audio-recorded, anonymized, transcribed verbatim, and thematically analyzed using qualitative methods. Results: Almost all participants described their role primarily as a health care provider, though some described themselves as 50-50 health care providers and retailers. Most staff pharmacists reported little control over front-of-store product selection. Where participants reported some control, external factors such as business viability and profitability impacted their choices, though some reported selecting products based on the needs of their patient community or their personal beliefs. The dominant tensions described stemmed from participants' dual roles as health care providers and retailers, though specific issues and situations were varied, ranging corporate targets, to service provision, to the sales of unproven or unhealthy products. Participants suggested solutions to the issues they described, ranging from a complete overhaul of the licensing structure of community pharmacies, down to one-on-one conversations with patients. Conclusion: Our findings suggest that the retail setting of community pharmacy produces unique ethical tensions: the imposition of retail sales standards and targets are commonplace, and business viability is a primary driving force in front-of-store product selection. Clear guidance from Canadian pharmacy colleges and legislators to address these tensions and issues may be necessary.